The Role of Epigenetic Modification in Regulating Lineage Commitment and Function in T regulatory Cells - Cameron, James. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2022-12.; Submitted to the Dept. of Immunology.; Advisor: Xudong Li.; Committee: Pilar Alcaide, Marta Gaglia, Alexander Poltorak, and Caroline Genco.; Keyword: Biology.